High-density AlN penetrating dislocation ultraviolet light-emitting device and preparation method thereof
By growing a through-dislocation array of high-density AlN film on the Al2O3 substrate, using dislocations as the luminescent unit, the problem of low luminescence efficiency of existing ultraviolet micro-nano light sources is solved, and small size, high integration and high luminescence are achieved UV light emitting devices with intensity, suitable for micro-nano-scale fields.
Patent Information
- Application Number
- CN202310817828.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-10
AI Technical Summary
The existing ultraviolet micro-nano light sources have low luminous efficiency and are difficult to achieve micron-scale AlGaN quantum dot micro-LEDs smaller than nanometers, which cannot meet the needs of high integration and high luminous intensity.
By growing a high-density AlN film on an Al2O3 substrate by pulsed laser deposition method, forming a through-dislocation array, and using dislocations as a light emitting unit, a small size and high light emitting intensity ultraviolet light emitting device is realized.
The preparation of high-density AlN through-dislocation ultraviolet luminescent devices has been realized, with small size, high integration and stable performance, and the luminous intensity is comparable to that of AlN body materials, and is suitable for the micro-nanoscale field.
Smart Images

Figure HDA0004322168530000011 
Figure HDA0004322168530000021
Abstract
Description
Technical field:
[0001] The present invention relates to the field of semiconductor micro-nano light-emitting devices, in particular to a high-density AlN through-dislocation ultraviolet light-emitting device and a preparation method thereof, which is suitable for the preparation of highly integrated, small-size, high-luminous-intensity micro-nano light-emitting devices. Background technology:
[0002] Ultraviolet light with a wavelength less than 400nm has been successfully applied to lighting, disinfection, air or water purification, and biomedical devices due to its short wavelength and high energy density. With the development of functional devices and the continuous improvement of integration, ultraviolet optoelectronic devices are developing towards smaller size, easier preparation, and longer service life to meet the needs of high-resolution quantum conversion displays, all-sky optical communications, and micro-nano sensor systems. So far, micro-nano light sources with ultraviolet wavelengths have only been obtained in AlGaN quantum dot-emitting micro-LEDs and color center luminescence in wide-bandgap semiconductors. Although AlGaN micro-LED devices and color center-emitting devices can emit ultraviolet light of different wavelengths, there are still many unavoidable limiting factors that lead to low luminescence efficiency. For example, the large lattice mismatch between AlGaN quantum dots and AlN buffer layers inevitably forms a high density of lattice defects. Moreover, with the reduction of size, the crystallinity of AlGaN quantum dot films with high Al content drops sharply. For these reasons, most AlGaN quantum dot micro-LEDs are micron-sized and rarely reach nanometer-sized. Therefore, it is of great significance to develop micro-nano ultraviolet light sources that are smaller in size, have stable luminous intensity, and can be excited by high-speed electrons, lasers or electric currents.
[0003] Dislocations are widely present in crystalline materials and play an important role in adjusting properties. Moreover, dislocations in functional materials often exhibit novel physical and chemical properties that are different from those of bulk materials. For example, Al2O3 dislocations can turn the material from an insulator into a conductor by doping Ti. At present, various techniques such as twin sintering and thin film heteroepitaxial engineering have been developed to regulate the type and density of dislocations. Therefore, it is promising to design and fabricate nanodevices based on the unique physical and chemical properties of dislocations in functional materials.
[0004] AlN has the advantages of wide bandgap, good thermal conductivity, stable chemical properties, and high luminescence efficiency, and is an excellent ultraviolet luminescent material. Since the atomic coordination number and chemical bonds in the AlN dislocation core are significantly different from those in bulk AlN, their band gap and luminescence wavelength should also be different from those in bulk, which makes AlN dislocations an outstanding candidate for micro-nano ultraviolet light sources. We use pulsed laser deposition (PLD) to grow high-quality AlN epitaxial films on Al2O3 substrates. The lattice mismatch between AlN and Al2O3 is about 12%, which leads to the formation of a density of about 4×10 10 cm-2 The AlN threading dislocation arrays. Cathodoluminescence (CL) spectroscopy shows that each individual AlN threading dislocation can act as a strong UV light source and work independently. A comprehensive study combining aberration-corrected transmission electron microscopy (TEM), atomic-resolution valence electron energy loss spectroscopy (EELS) and first-principles calculations was performed to clarify the atomic origin of dislocation UV emission, which broadens the direction for the practical application of dislocations as light-emitting devices in the future. Summary of the invention:
[0005] The purpose of the present invention is to provide a high-density AlN through-dislocation ultraviolet light-emitting device and a preparation method thereof. The light-emitting device uses through-dislocations as light-emitting units and has the characteristics of small size, high luminous intensity and stable performance, in order to solve the development bottleneck of semiconductor materials in current research and provide a new design idea for light-emitting devices, laying a foundation for the design and application of new micro-nano light-emitting devices.
[0006] The technical solution of the present invention is:
[0007] A high-density AlN threading dislocation ultraviolet light-emitting device is disclosed. The AlN film is a semiconductor material with the widest band gap, and the band gap is 6.2 eV. Moreover, AlN has a direct band gap and is selected as the most ideal deep ultraviolet light-emitting material, and the emission wavelength is 212 nm. The AlN film is grown on an Al2O3 (0001) single crystal substrate by a pulsed laser deposition method. There is a large lattice mismatch between the AlN film and the Al2O3 substrate, and a high-density threading dislocation array is formed in the grown AlN film. By adjusting the lattice mismatch between the Al2O3 substrate and the AlN film, the density of the threading dislocation array in the AlN film is effectively controlled to be 5×10 9 ~4×10 10 / cm 2 These dislocations nucleate on the AlN / Al2O3 heterointerface and run through the entire AlN film. The changes in the coordination number and bond length of Al and N atoms at the dislocation core cause the dislocation to produce 317nm ultraviolet light, which is different from that of the AlN bulk material, forming a micro-nano light-emitting device with dislocations as light-emitting units.
[0008] The method for preparing the high-density AlN through-dislocation ultraviolet light-emitting device comprises the following specific steps:
[0009] First, the Al2O3 (0001) single crystal substrate was annealed in air at 1000℃~1500℃ for 3h~5h to obtain an atomically flat surface. Then, the treated Al2O3 substrate was transferred to a growth chamber and AlN thin film was grown on the Al2O3 (0001) single crystal substrate using a pulsed laser deposition system. The AlN thin film growth parameters were: growth temperature 700℃~900℃, laser energy 2J / cm 2~4.5J / cm 2 , laser frequency 3Hz~6Hz, nitrogen partial pressure 1×10 -6 Pa~1×10 -3 Pa, the substrate-target distance is 6cm-8cm; finally, the grown AlN film is slowly cooled to room temperature in a high-purity N2 atmosphere, and a high-quality single crystal epitaxial AlN film is obtained.
[0010] In the method for preparing the high-density AlN through-dislocation ultraviolet light-emitting device, during the process of growing an AlN film in a pulsed laser deposition system, the target material used is an AlN compound prepared by hot isostatic pressing.
[0011] In the preparation method of the high-density AlN threading dislocation ultraviolet light-emitting device, during the pulse laser deposition process, the deposition time is 10 minutes to 10 hours, and the thickness of the grown AlN film is 20nm to 1.7μm.
[0012] The method for preparing the high-density AlN through-dislocation ultraviolet light-emitting device, after the AlN film is deposited, is placed in a 1×10 2 Pa~5×10 3 Pa's high-purity N2 atmosphere is slowly cooled to room temperature at a cooling rate of 200-400℃ / h.
[0013] In the method for preparing a high-density AlN threading dislocation ultraviolet light-emitting device, there is a 12% lattice mismatch between the AlN film and the Al2O3 substrate, resulting in high-density threading dislocations in the grown AlN film; wet etching shows that the density of the threading dislocation array in the AlN film is 5×10 9 ~4×10 10 / cm 2 .
[0014] The preparation method of the high-density AlN through-dislocation ultraviolet light-emitting device adopts KOH aqueous solution for dislocation wet etching, the concentration of the etching solution is 3mol / L-10mol / L, the etching temperature is 50℃-100℃, and the etching time is 10s-600s.
[0015] The method for preparing the high-density AlN through-dislocation ultraviolet light-emitting device measures the light-emitting behavior at the dislocation by a cathode fluorescence spectrometer, and finds that the dislocation light-emitting wavelength is 317nm, the AlN bulk material light-emitting wavelength is 212nm, and the dislocation light-emitting intensity is equivalent to that of the AlN bulk material.
[0016] The method for preparing the high-density AlN through-dislocation ultraviolet light-emitting device changes the coordination number of Al and N atoms and the Al-N bond length at the dislocation core, significantly reducing the band gap at the dislocation core, thereby causing ultraviolet light emission at a wavelength of 317nm at the dislocation.
[0017] The design concept of the present invention is:
[0018] The present invention firstly grows high-quality epitaxial AlN film on Al2O3 (0001) single crystal substrate using pulsed laser deposition system. Due to the large lattice mismatch (~12%) between AlN film and Al2O3 substrate, ~10 10 / cm 2 High-density through-dislocation array. The change of the coordination number of Al and N atoms and the Al-N bond length at the core of the through-dislocation significantly reduces the band gap at the core of the dislocation, showing a luminescence wavelength different from that of the AlN bulk material, thereby realizing through-dislocation ultraviolet luminescence. The luminescence behavior at the dislocation is measured by a cathode fluorescence spectrometer, and it is found that the dislocation luminescence wavelength is 317nm, the luminescence wavelength of the AlN bulk material is 212nm, and the dislocation luminescence intensity is equivalent to that of the AlN bulk material. In principle, AlN through-dislocation ultraviolet luminescence is realized, and a single dislocation can work independently. The present invention uses a pulsed laser deposition method to epitaxially grow a high-quality single-crystal AlN film on an Al2O3 (0001) single crystal substrate, and realizes dislocation luminescence by changing the coordination number and chemical bond of the dislocation core, thereby realizing the design of a micro-nano-sized dislocation ultraviolet luminescent device with small size, high integration, stable luminescence performance and high luminescence intensity. The design of this micro-nano luminescent device using dislocation as the main luminescent unit lays a foundation for the application of small-sized optoelectronic devices and sensor devices.
[0019] The advantages and beneficial effects of the present invention are:
[0020] 1. The present invention proposes a high-density AlN through-dislocation ultraviolet light-emitting device, which has a high-quality AlN film with simple preparation process and stable performance. The light-emitting device has a small size, high integration and high luminous intensity.
[0021] 2. The present invention proposes a high-density AlN through-dislocation ultraviolet light-emitting device with high luminous intensity, micro-nano level luminous size and high integration. It is a new functional device that uses dislocations as light-emitting units. This series of structural and functional characteristics lays the foundation for the development of this new type of dislocation micro-nano light-emitting device in fields related to high-resolution displays, quantum communications and micro-photoelectric sensors.
[0022] 3. The present invention proposes a high-density AlN through-dislocation ultraviolet light-emitting device with a simple growth process, easy operation, high material crystal quality, and large-scale batch production.
[0023] 4. Compared with other traditional light-emitting devices, the high-density AlN through-dislocation ultraviolet light-emitting device obtained by the present invention has the characteristics of smaller size, higher integration, short emission wavelength, and high emission intensity because it uses dislocations as light-emitting units. Its device preparation can be applied in micro-nanoscale fields.
[0024] 5. The high-density AlN through-dislocation ultraviolet light-emitting device obtained by the present invention provides a new idea for the development of semiconductor materials in the field of optoelectronic devices and their application in the field of functional devices, and lays a foundation for the development of new micro-nano light-emitting devices in the fields of displays, communications and sensors. Description of the drawings:
[0025] Figure 1 Schematic diagram of the generation of high-density through-dislocation arrays and through-dislocation luminescence in AlN films grown on Al2O3 substrates by pulsed laser deposition systems. (a) is a schematic diagram of the growth of AlN films on Al2O3 substrates; (b) is a schematic diagram of dislocation ultraviolet luminescence; (c) is a scanning secondary electron image of the grown AlN film; (d) is a CL spectrum of the AlN film, where the horizontal axis Wavelength represents the wavelength (nm) and the vertical axis Intensity represents the relative luminescence intensity (au).
[0026] Figure 2 Figures (a)-(c) are schematic diagrams of the etching morphology of edge, screw and mixed dislocations in AlN films; Figures (d)-(f) are scanning secondary electron images of edge, screw and mixed dislocations after wet etching; Figures (g)-(i) are surface scans of CL luminescence intensity of edge, screw and mixed dislocations. Specific implementation method:
[0027] In the specific implementation process, the present invention proposes a high-density AlN through-dislocation ultraviolet light-emitting device and a preparation method thereof. An AlN film is grown on an Al2O3 (0001) single crystal substrate by a pulsed laser deposition system. The large lattice mismatch between the AlN film and the Al2O3 substrate forms a high-density through-dislocation array in the film. The through-dislocation array can be used as a structural unit of the ultraviolet light-emitting device. The specific steps are as follows:
[0028] (1) Preparation of AlN thin film: AlN thin film was grown on Al2O3 substrate by pulsed laser deposition system. The specific growth parameters are as follows;
[0029] The Al2O3 rod-shaped single crystal was grown by the mature Czochralski method, with a purity of >99.99wt% and an axial orientation of (0001). After mechanical cutting and precision polishing, a 10×10×0.5mm single crystal wafer was obtained. The surface roughness of the Al2O3 single crystal wafer was < In order to obtain an atomically flat surface, the Al2O3 substrate is annealed in the air at 1300℃~1500℃ for 3h~5h, preferably 1500℃ for 3h, to obtain the best Al2O3 surface quality. The treated Al2O3 substrate is then quickly transferred to the deposition chamber to prepare for the next step of AlN film growth. The AlN film is grown by a pulsed laser deposition system, in which the laser is COMPex-201, with a wavelength of 248nm, a pulse width of 25ns, and a growth frequency that can be continuously adjusted in the range of 1Hz to 10Hz. During the growth process, the N2 partial pressure is 1×10 -6 Pa~1×10 -3 Pa high vacuum (preferably 1×10 -4 Pa), the growth temperature is 700℃~900℃ (preferably 800℃), and the laser energy is 2J / cm 2 ~4.5J / cm 2 (Preferably 3J / cm 2 ), the frequency of laser bombardment of AlN target is 4 Hz, the distance between substrate and target is 6 cm to 8 cm (preferably 7 cm), the growth time is 10 min to 10 h, the thickness of grown AlN film is 20 nm to 1.7 μm, and high-quality single crystal epitaxial AlN film growth is completed.
[0030] (2) To maintain a good stoichiometric ratio of the grown AlN film, the AlN film is 2 Pa~5×10 3 Pa (preferably 4×10 2 Pa) in an atmosphere of high-purity N2 (volume purity 99.999%), and slowly cooled to room temperature at a cooling rate of 300°C / h and a cooling time of about 2.7h, at which time an AlN dislocation Wiener light-emitting device can be obtained.
[0031] The high-density AlN threading dislocation ultraviolet light-emitting device obtained by the present invention has an AlN film with extremely high crystal quality, a film thickness of 200nm to 1.7μm, and satisfies a good stoichiometric ratio. There is a large lattice mismatch between the AlN film and the Al2O3 substrate, and there must be a high-density threading dislocation array in the film. After wet etching, it can be found that the density of dislocations in the AlN film is about 4×10 10 / cm 2Since the AlN film and Al2O3 substrate materials have stable physical properties and uniform composition, and the AlN film is grown epitaxially, large-scale and batch production is expected to be achieved.
[0032] The present invention is further described in detail below through examples and drawings.
[0033] Example 1
[0034] like Figure 1 and Figure 2 As shown, the high-density AlN through-dislocation ultraviolet luminescence and the preparation method thereof of this embodiment are as follows:
[0035] First, the present invention uses a pulsed laser deposition system to prepare high-quality AlN film. Before the growth of the AlN film, we first performed high-temperature annealing on the Al2O3 (0001) single crystal substrate in air to obtain an atomically flat surface. Among them, the annealing temperature of the Al2O3 (0001) single crystal substrate is 1500°C, and the annealing time is 3h. AlN film growth parameters: The substrate for AlN film growth is a high-temperature annealed Al2O3 (0001) single crystal substrate, the substrate size is 10×10×0.5mm, the substrate purity is >99.99wt%, the growth temperature is 800°C, and the pulse laser energy is 3J / cm 2 The pulse frequency is 4Hz. Focused high-energy laser bombards the AlN target, causing the atomic layer on the surface of the AlN target to be peeled off to form plasma glow, which diffuses to the substrate and combines with the atoms on the surface of the substrate to finally form a high-quality AlN film. -4 After the AlN film was grown for 30 min in a Pa atmosphere, the film thickness reached 60 nm. 2 Pa in a N2 atmosphere and slowly cooled to room temperature at a cooling rate of 300°C / hour. High-resolution X-ray diffractometer, X-ray photoelectron spectroscopy, Raman spectroscopy and transmission electron microscopy were used to characterize the film's crystalline quality, micromorphology, chemical composition, and atomic and electronic structure of AlN through-dislocations. It was found that a different core structure was formed at the core of the through-dislocation, the coordination number and bond length of Al and N atoms changed significantly compared to the bulk, and the band gap at the dislocation core was significantly reduced.
[0036] Subsequently, the AlN film was wet-etched using a 5 mol / L KOH aqueous solution, and the type of AlN threading dislocation can be easily determined based on the secondary electron image of the etching morphology. The luminescence behavior of a single AlN threading dislocation was measured using a cathode fluorescence spectrometer integrated in a scanning electron microscope. It was found that in addition to the intrinsic luminescence peak of 212 nm, the AlN film also produced a dislocation luminescence peak with a luminescence intensity comparable to that of the AlN bulk material and a luminescence wavelength of 212 nm. Different types of threading dislocations can all achieve independent luminescence, among which edge dislocations have the highest luminescence intensity, followed by screw dislocations, and mixed dislocations have the weakest luminescence intensity. Therefore, this provides ideas for the preparation of ultraviolet light-emitting devices using AlN threading dislocations as luminescent units.
[0037] Example 2
[0038] like Figure 1 and Figure 2 As shown, the high-density AlN through-dislocation ultraviolet luminescence and the preparation method thereof of this embodiment are as follows:
[0039] First, the present invention uses a pulsed laser deposition system to prepare high-quality AlN film. Before the growth of the AlN film, we first performed high-temperature annealing on the Al2O3 (0001) single crystal substrate in air to obtain an atomically flat surface. Among them, the annealing temperature of the Al2O3 (0001) single crystal substrate is 1500°C, and the annealing time is 3h. AlN film growth parameters: The substrate for AlN film growth is a high-temperature annealed Al2O3 (0001) single crystal substrate, the substrate size is 10×10×0.5mm, the substrate purity is >99.99wt%, the growth temperature is 800°C, and the pulse laser energy is 3J / cm 2 The pulse frequency is 4Hz. Focused high-energy laser bombards the AlN target, causing the atomic layer on the surface of the AlN target to be peeled off to form plasma glow, which diffuses to the substrate and combines with the atoms on the surface of the substrate to finally form a high-quality AlN film. -4 After the AlN film was grown for 5 hours in a Pa atmosphere, the film thickness reached 1.0 μm. 2 Pa in a N2 atmosphere and slowly cooled to room temperature at a cooling rate of 300°C / hour. High-resolution X-ray diffractometer, X-ray photoelectron spectroscopy, Raman spectroscopy and transmission electron microscopy were used to characterize the film's crystalline quality, micromorphology, chemical composition, and atomic and electronic structure of AlN through-dislocations. It was found that a different core structure was formed at the core of the through-dislocation, the coordination number and bond length of Al and N atoms changed significantly compared to the bulk, and the band gap at the dislocation core was significantly reduced.
[0040] Subsequently, the AlN film was wet-etched using a 5 mol / L KOH aqueous solution, and the type of AlN threading dislocation can be easily determined based on the secondary electron image of the etching morphology. The luminescence behavior of a single AlN threading dislocation was measured using a cathode fluorescence spectrometer integrated in a scanning electron microscope. It was found that in addition to the intrinsic luminescence peak of 212 nm, the AlN film also produced a dislocation luminescence peak with a luminescence intensity comparable to that of the AlN bulk material and a luminescence wavelength of 212 nm. Different types of threading dislocations can all achieve independent luminescence, among which edge dislocations have the highest luminescence intensity, followed by screw dislocations, and mixed dislocations have the weakest luminescence intensity. Therefore, this provides ideas for the preparation of ultraviolet light-emitting devices using AlN threading dislocations as luminescent units.
[0041] Example 3
[0042] like Figure 1 and Figure 2 As shown, the high-density AlN through-dislocation ultraviolet luminescence and the preparation method thereof of this embodiment are as follows:
[0043] First, the present invention uses a pulsed laser deposition system to prepare high-quality AlN film. Before the growth of the AlN film, we first performed high-temperature annealing on the Al2O3 (0001) single crystal substrate in air to obtain an atomically flat surface. Among them, the annealing temperature of the Al2O3 (0001) single crystal substrate is 1500°C, and the annealing time is 3h. AlN film growth parameters: The substrate for AlN film growth is a high-temperature annealed Al2O3 (0001) single crystal substrate, the substrate size is 10×10×0.5mm, the substrate purity is >99.99wt%, the growth temperature is 800°C, and the pulse laser energy is 3J / cm 2 The pulse frequency is 4Hz. Focused high-energy laser bombards the AlN target, causing the atomic layer on the surface of the AlN target to be peeled off to form plasma glow, which diffuses to the substrate and combines with the atoms on the surface of the substrate to finally form a high-quality AlN film. -4 After 10 hours of growth in Pa atmosphere, the film thickness reached 1.7 μm. 2 Pa in a N2 atmosphere and slowly cooled to room temperature at a cooling rate of 300°C / hour. High-resolution X-ray diffractometer, X-ray photoelectron spectroscopy, Raman spectroscopy and transmission electron microscopy were used to characterize the film's crystalline quality, micromorphology, chemical composition, and atomic and electronic structure of AlN through-dislocations. It was found that a different core structure was formed at the core of the through-dislocation, the coordination number and bond length of Al and N atoms changed significantly compared to the bulk, and the band gap at the dislocation core was significantly reduced.
[0044] Subsequently, the AlN film was wet-etched using a 5 mol / L KOH aqueous solution, and the type of AlN threading dislocation can be easily determined based on the secondary electron image of the etching morphology. The luminescence behavior of a single AlN threading dislocation was measured using a cathode fluorescence spectrometer integrated in a scanning electron microscope. It was found that in addition to the intrinsic luminescence peak of 212 nm, the AlN film also produced a dislocation luminescence peak with a luminescence intensity comparable to that of the AlN bulk material and a luminescence wavelength of 212 nm. Different types of threading dislocations can all achieve independent luminescence, among which edge dislocations have the highest luminescence intensity, followed by screw dislocations, and mixed dislocations have the weakest luminescence intensity. Therefore, this provides ideas for the preparation of ultraviolet light-emitting devices using AlN threading dislocations as luminescent units.
[0045] like Figure 1 As shown in the figure, a schematic diagram of the generation of high-density through-dislocation arrays and through-dislocation luminescence in AlN films grown on Al2O3 substrates by a pulsed laser deposition system. Among them, (a) is a schematic diagram of the growth of AlN thin film (Thin film) on Al2O3 substrate (Substrate). Due to the large lattice mismatch between the two, a large number of through-dislocations (Dislocation) are formed in the film. (b) is a schematic diagram of the ultraviolet luminescence of dislocations. First, the electrons in the film are excited to transition from the top of the valence band (Valence Band) to the bottom of the conduction band (Conduction Band). When the excited electrons are captured by the dislocation (Dislocation) during the fall back process, the electrons and holes recombine at the dislocation, thereby realizing dislocation luminescence. (c) is a scanning secondary electron image of the grown AlN film. Through the selective etching of dislocations (Dislocation), the dislocations appear as dots in the scanned image (SEM image). According to statistics, the density of the through-dislocation array in the AlN film is 4×10 10 cm -2 (d) is the CL spectrum of AlN film. It can be seen from the figure that in addition to the 212nm intrinsic luminescence peak of AlN film, a dislocation luminescence peak with a wavelength of 317nm is also generated. Moreover, the dislocation luminescence intensity is comparable to that of AlN bulk. Dislocation luminescence is mainly caused by the change of coordination number and bonding at the dislocation core.
[0046] like Figure 2As shown, the luminescence image of a single dislocation. Among them, (a)-(c) are schematic diagrams of the etching morphology of edge, screw and mixed dislocations in AlN films. It can be seen from the figure that the edge dislocation forms a hexagonal pyramid etching morphology, the screw dislocation forms a hexagonal pyramid etching morphology, and the mixed dislocation has the etching morphology characteristics of both edge and screw dislocations. (d)-(f) are scanning secondary electron images of edge, screw and mixed dislocations after wet etching, respectively. It can be seen that the experimental etching morphology is perfectly consistent with the model ac. (g)-(i) are scanning images of the CL emission surface of edge, screw and mixed dislocations, respectively. It can be clearly seen from the figure that the three types of dislocations can achieve independent luminescence at a wavelength of 317nm. The edge dislocation has the highest luminescence intensity, followed by the screw type, and the mixed type has the weakest luminescence intensity. This lays the foundation for the preparation of ultraviolet devices with dislocations as light-emitting units.
[0047] The above results show that the present invention achieves the growth of high-quality AlN epitaxial film through the pulsed laser deposition system. Due to the large lattice mismatch between the film and the substrate, high-density threading dislocations are generated in the AlN film, which lays the foundation for the preparation of ultraviolet light-emitting devices with dislocations as light-emitting units. The preparation process of this Wiener-scale high-density AlN threading dislocation ultraviolet light-emitting device is simple and easier to control, thus laying the foundation for research and application in the fields of small-size, high-integration displays, information communications, and micro-photoelectric sensors.
Claims
1. A high-density AlN through-dislocation ultraviolet light-emitting device, characterized in that: AlN film is the semiconductor material with the widest band gap, with a band gap of 6.2eV. Moreover, AlN has a direct band gap, so AlN is selected as the most ideal deep ultraviolet luminescent material with a luminescent wavelength of 212nm. AlN film is grown on Al2O3 (0001) single crystal substrate by pulsed laser deposition method. There is a large lattice mismatch between AlN film and Al2O3 substrate, and a high-density threading dislocation array is formed in the grown AlN film. By adjusting the lattice mismatch between Al2O3 substrate and AlN film, the density of threading dislocation array in AlN film is effectively controlled to 5×10 9 ~4×10 10 / cm 2 These dislocations nucleate on the AlN / Al2O3 heterointerface and run through the entire AlN film. The changes in the coordination number and bond length of Al and N atoms at the dislocation core cause the dislocation to produce 317nm ultraviolet light, which is different from that of the AlN bulk material, forming a micro-nano light-emitting device with dislocations as light-emitting units.
2. A method for preparing a high-density AlN threading dislocation ultraviolet light-emitting device according to claim 1, characterized in that: The specific steps are as follows: First, the Al2O3 (0001) single crystal substrate was annealed in air at 1000℃~1500℃ for 3h~5h to obtain an atomically flat surface. Then, the treated Al2O3 substrate was transferred to a growth chamber and AlN thin film was grown on the Al2O3 (0001) single crystal substrate using a pulsed laser deposition system. The AlN thin film growth parameters were: growth temperature 700℃~900℃, laser energy 2J / cm 2 ~4.5J / cm 2 , laser frequency 3Hz~6Hz, nitrogen partial pressure 1×10 -6 Pa~1×10 -3 Pa, the substrate-target distance is 6cm-8cm; finally, the grown AlN film is slowly cooled to room temperature in a high-purity N2 atmosphere, and a high-quality single crystal epitaxial AlN film is obtained.
3. The method for preparing a high-density AlN threading dislocation ultraviolet light-emitting device according to claim 2, characterized in that: In the process of growing AlN thin films using a pulsed laser deposition system, the target material used is an AlN compound prepared by hot isostatic pressing.
4. The method for preparing a high-density AlN threading dislocation ultraviolet light-emitting device according to claim 2, characterized in that: During the pulse laser deposition process, the deposition time is 10 min to 10 h, and the thickness of the grown AlN film is 20 nm to 1.7 μm.
5. The method for preparing a high-density AlN threading dislocation ultraviolet light-emitting device according to claim 2, characterized in that: After the AlN film deposition, place it in 1×10 2 Pa~5×10 3 Pa's high-purity N2 atmosphere is slowly cooled to room temperature at a cooling rate of 200-400℃ / h.
6. The method for preparing a high-density AlN threading dislocation ultraviolet light-emitting device according to claim 2, characterized in that: There is a 12% lattice mismatch between the AlN film and the Al2O3 substrate, which leads to a high density of threading dislocations in the grown AlN film. Through wet etching, it is found that the density of the threading dislocation array in the AlN film is 5×10 9 ~4×10 10 / cm 2 .
7. The method for preparing a high-density AlN threading dislocation ultraviolet light-emitting device according to claim 6, characterized in that: The dislocation wet etching uses a KOH aqueous solution, the concentration of the etching solution is 3 mol / L to 10 mol / L, the etching temperature is 50° C. to 100° C., and the etching time is 10s to 600s.
8. The method for preparing a high-density AlN threading dislocation ultraviolet light-emitting device according to claim 2, characterized in that: The luminescence behavior at the dislocation was measured using a cathode fluorescence spectrometer, and it was found that the dislocation luminescence wavelength was 317nm, the luminescence wavelength of the AlN bulk material was 212nm, and the dislocation luminescence intensity was comparable to that of the AlN bulk material.
9. The method for preparing a high-density AlN threading dislocation ultraviolet light-emitting device according to claim 2, characterized in that: The coordination number of Al and N atoms and the Al-N bond length at the dislocation core change, which significantly reduces the band gap at the dislocation core, resulting in ultraviolet light emission at a wavelength of 317nm at the dislocation.